(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Financial Inclusion refers to provide affordable financial services – such as banking, credit, insurance and digital payments-to all individuals and businesses, especially, those traditionally underserved. Micro, Small and Medium Enterprises (MSME)from the backbone of developing economy, contributing significantly to employment generation, Innovation and GDP growth. Financial Inclusion enhances the development of MSMEs by improving access to essential financial services like credit, savings and digital payments, which boosts their performance, facilitates expansion, promote employment and contributes to their overall sustainability. This study aims to explore the impact of Financial Inclusion on the Micro, Small and Medium enterprises’ (MSMEs) in its development and growth in India. This study takes into account the schemes launched by the Indian Government which are majorly contributing to the growth of these MSMEs. This study also evaluate the impact of digital financial services on MSME. It identifies challenges faced by MSMEs in accessing inclusive finance and also suggests policy measure for strengthening financial inclusion to promote industrial growth. The data-analysis is exclusively done based on the secondary sources of data collected from articles, textbooks, journals, websites, annual reports of MSMEs &published press releases made by the Government officially via the Press Information Bureau.